Regulating recycling in Malaysia / Muhammad Zulhilmi Zahin Ahmad, Wan Myra Dyana and Muhammad Asyraf Azni - Ahmad, Muhammad Zulhilmi Zahin; Dyana, Wan Myra; Azni, Muhammad Asyraf (2012)
Recycling is not a new thing for Malaysian. In fact we had been exposed to the government advertisement campaigns twice, in 1993 and 2000. Reduce, recycle and reuse is a common word used in promoting recycle activities by the environmentalists, but unfortunately it seems like the nationwide campaign failed to give a meaningful change for the nature. Most of Malaysian do not have the awareness or even took a minimal effort to take a better care for the environment. Thus, we would like to propose for regulating a new effective law that makes it mandatory for Malaysian to recycle. Solid Waste and Public Cleansing Management Act 2007 (Malaysia) has been amended to provide a better solid waste management. In West Malaysia only, the law had finally been enforced on September 2011. Section 101 of the Act provides the Minister may, by order published in the Gazette, to requires any person, to use specified amount of recycled materials, to implement a coding and labelling systems for any product or material to promote recycling, and to use of any method or manner for the purpose of reduction, reuse and recycling of the controlled solid waste. Whereas section 102 of the same Act provided that the Minister may, by order published in the Gazette to establish a "take back system" in which require that any specified products or goods that after used shall be taken back by the manufacturer, assembler, importer or dealer and that they must be obliged on their own account and cost to recycle or dispose any products or goods taken back in a specified manner.1 This is a good first step taken by the government in amending a recycling law in Malaysia. However, more is needed to gevern recycling as there are other aspects of recycling that are not governed under this Act. For example, there should be a mandatory requirement to all person in Malaysia to recycle.